Valores hematológicos e bioquímicos para aves de rapina atendidas na Grande Cuiabá/MT - Rocha, Marcela Natacha Aparecida (2021)
Brazil is one of the countries that concentrates the largest number of species of predators in the world whose increase in the number of veterinary medical care for this group derives, predominantly, as a consequence of anthropic actions. Blood tests have an important role in the poultry clinic, especially in monitoring their health, and the comparison with data obtained from healthy populations is of great importance for the diagnosis / clinical prognosis. Thus, the objectives of this work were to describe hematological and biochemical values for healthy birds of prey received by environmental agencies in Cuiabá and Várzea Grande / MT. 71 samples were collected from 13 different species of predators between November 2018 and November 2019. The mean descriptive hematological (n = 71) and biochemical (n = 47) values and standard deviations were determined in six different species using Microsoft software Excel®, with the Reference Value Advisor supplement (version 2.1) and, in four other species, the values presented for each of these parameters were only observable. Of the 13 species analyzed, hematological and biochemical values of the species Glaucidium brasilianum (Strigidae), Herpetotheres cachinnans (Falconidae) and Urubutinga urubutinga (Accipitridae) were described for the first time in this study. The values of hematological and biochemical parameters of the other free-living species studied differ, for the most part, from those described for raptors in captivity.